Peran Wakaf dalam Pengembangan Ekonomi Berkelanjutan: Studi Kasus di Indonesia - Siti Masruroh; Eduardus Nanggur; Ulrianus Aristo Ngamal (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study explores the role of waqf in sustainable economic development in Indonesia, the country with the largest Muslim population in the world. Waqf, as a form of Islamic philanthropy, has great potential to support sustainable development but has yet to be fully utilized in Indonesia. Using a qualitative approach and case study method through interviews, documentation, and observation in Jakarta, Yogyakarta, and Surabaya, this study found that waqf contributes significantly to the education and health sectors, funding schools, universities, hospitals, and clinics. Waqf also supports the development of small and medium enterprises (SMEs), infrastructure development, and environmentally friendly projects. However, waqf management faces challenges such as lack of public understanding, limited regulation, and ineffective management. To improve the effectiveness and transparency of waqf management, regulatory reform and capacity building of managers through education and training are needed. Community participation can be increased through more intensive education and socialization programs, as well as collaboration with the government and private sector. This research is expected to provide in-depth insights into the role of waqf in sustainable economic development and offer solutions to overcome the existing challenges